Identifikasi dan Deskripsi Tanaman Umbi-Umbian Pengganti Karbohidrat di Kabupaten Trenggalek - Evy Latifah; PER Prahardini (Agrosains : Jurnal Penelitian Agronomi, 2020)
The programs to increased food diversification through policies to accelerate diversification of food consumption based on local resources as a substitute for rice. The tubers that have been widely used by the community are cassava, sweet potato and potato. However, there are still many other yam plants that have not been maximally utilized and developed.  Thus it is necessary to carry out research aimed at knowing the identification and description of tuber crops, especially in several sub-districts in Trenggalek Regency. The determination of the research area was carried out by using purposive sampling method by coordinating with the Trenggalek Regency Agriculture Office, then to obtain data on the potential area of tubers was carried out by sampling using the snowball sampling method. From the results of the study, it is known that Munjungan sub-district is one of the districts that has the most land area (154.80 km2) compared to other sub-districts in Trenggalek Regency so that it is able to produce the production of several tuber commodities including uwi, gembili, gadung, suweg and bentoel so it needs development for this tubers in the region.